1979
DOI: 10.1007/bf02618249
|View full text |Cite
|
Sign up to set email alerts
|

A growth history comparison of the human diploid cells WI-38 and IMR-90: Proliferative capacity and cell sizing analysis

Abstract: Results of growth history studies on IMR-90 and WI-38 showed that the two cell strains were equivalent in population doublings achieved per life span. However, IMR-90 exhibited higher cell yields in phase II than did WI-38. In addition, entry of IMR-90 cells into phase III occurred more abruptly than in WI-38 cultures. Cell sizing analysis showed that phase II and phase III IMR-90 cell populations contained greater numbers of cells in the small volume categories. At senescence, both cell lines contained simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…Senescence is defined as the loss ofproliferative capacity ofthe cultures and results in the inability of the population to increase in cell number typically after cultures have been passaged 50 or more times. Senescence is associated with a number of gross cellular changes including cell-cycle arrest (3,4), increase in cell size and size heterogeneity (5)(6)(7)(8), and increase in the frequency of cells with chromosomal aberrations, including polyploidy (9)(10)(11)(12). However, molecular data indicate that young and senescent cells do not consistently differ in the pattern of regulation of genes that are sensitive to serum stimulation (13) and several aspects of DNA replication have been reported not to change with culture age (14,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Senescence is defined as the loss ofproliferative capacity ofthe cultures and results in the inability of the population to increase in cell number typically after cultures have been passaged 50 or more times. Senescence is associated with a number of gross cellular changes including cell-cycle arrest (3,4), increase in cell size and size heterogeneity (5)(6)(7)(8), and increase in the frequency of cells with chromosomal aberrations, including polyploidy (9)(10)(11)(12). However, molecular data indicate that young and senescent cells do not consistently differ in the pattern of regulation of genes that are sensitive to serum stimulation (13) and several aspects of DNA replication have been reported not to change with culture age (14,15).…”
mentioning
confidence: 99%
“…In this figure, the first panel in each row presents the size distribution of the entire cell population (90LS), which as in Fig. 1 (6,21). Senescence of IMR-90 cell populations reflects the progressive change in the relative proportion of these two components of the cell population (22).…”
mentioning
confidence: 99%
“…In general, since saturation density declines with increasing PDL (Houghton and Stidworthy, 1979;Matuoka and Mitsui, 1981;Macieira-Coelho and Azzarone, 1982;Greenberg et al, 1977; our own data not shown), the results of experiments using older cultures were CM, 6-day conditioned medium containing 10% FBS; 5FM, fresh medium containing 5% FBS; BMFM, fresh medium containing 2M% FBS; 1CM:l S-F, 1 part CM to 1 part serum-free medium; 1CM3 S-F, 1 part CM to 3 parts serum-free medium.…”
Section: 0mentioning
confidence: 95%
“…The cell life span is defined in the literature as the ability of the epithelial cells to undergo maximum number of divisions in response to injury in order to reconstruct the tissue of origin (Absher et al 1974, Houghton and Stidworthy 1979, Muggleton-Harris and DeSimone 1980 . The average of this maximum number is about 50 .…”
Section: Life Span Of the Stem Cells Tmentioning
confidence: 99%